Automatically Identifying Sickness Behavior in Grazing Lambs with an Acceleration Sensor - Bowen Fan; Racheal H. Bryant; Andrew W. Greer (Animals, 2023)
Acute disease of grazing animals can lead to alterations in behavioral patterns. Relatively recent advances in accelerometer technology have resulted in commercial products, which can be used to remotely detect changes in animals’ behavior, the pattern and extent of which may provide an indicator of disease challenge and animal health status. The objective of this study was to determine if changes in behavior during use of a lipopolysaccharide (LPS) challenge model can be detected using ear-mounted accelerometers in grazing lambs. LPS infusion elevated rectal temperatures from 39.31 °C to 39.95 °C, indicating successful establishment of an acute fever response for comparison with groups (p < 0.001). For each of the five recorded behaviors, time spent eating, ruminating, not active, active, and highly active, the accelerometers were able to detect an effect of LPS challenge. Compared with the control, there were significant effects of LPS infusion by hour interaction on durations of eating (−6.71 min/h, p < 0.001), inactive behavior (+16.00 min/h, p < 0.001), active behavior (−8.39 min/h, p < 0.001), and highly active behavior (−2.90 min/h, p < 0.001) with a trend for rumination time (−1.41 min/h, p = 0.075) in lambs after a single LPS infusion. Results suggest that current sensors have the capability to correctly identify behaviors of grazing lambs, raising the possibility of detecting changes in animals’ health status.